"I Have More in Common with Americans Than I Do with Illegal Aliens": Culture, Perceived Threat, and Neighborhood Preferences. Issue 3 (July 2015) - Meyerhoffer, Cassi A.
In this article, I explore different forms of perceived threat posed by the presence of minority groups and how threat impacts residential segregation and neighborhood preferences. I extend previous research by exploring non-Hispanic white residents' preferences regarding black and Latino neighbors using qualitative data from in-depth interviews with white adults conducted in multiple neighborhoods in Buffalo, New York, and Ogden, Utah. My findings suggest that white residents perceive threat differently for blacks and Latinos. In general, blacks and Latinos elicit crime threat but Latinos also elicit concerns about a cultural threat to dominant American culture. I distinguish between perceived threat in neighborhood preferences based on: (1) perceived threat to individuals surrounding personal safety and neighborhood conditions and (2) perceived threats to national identity and economic well-being of the state. Several studies have looked at the role of cultural threat in how whites perceive racial and ethnic minorities; however, few studies look at how this threat affects neighborhood preferences specifically. Studying blacks and Latinos sheds new light on how multiple forms of perceived threat affect whites' neighborhood preferences.